2010
DOI: 10.1186/1472-6963-10-136
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare costs associated with progressive diabetic retinopathy among National Health Insurance enrollees in Taiwan, 2000-2004

Abstract: BackgroundDiabetic retinopathy is one of the most common microvascular complications of diabetes and one of the major causes of adult visual impairment in national surveys in Taiwan. This study aimed to identify the healthcare costs of Taiwan's National Health Insurance program on behalf of diabetic patients with stable or progressive retinopathy.MethodsA retrospective cohort study was conducted with 4,988 medication-using diabetic retinopathy subjects ≥ 40 years of age under National Health Insurance Program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Most existing studies have adopted the cross-section study design and reported only point estimates of annual prevalence of diabetic complications and associated costs (Chang, Weiner, Richards, Bleich, & Segal, 2012a;Rosenzweig, Weinger, Poirier-Solomon, & Rushton, 2002;Ward, Alvarez, Vo, & Martin, 2014). Furthermore, some of them were limited to specific diabetic complications (such as cardiovascular complications (Straka, Liu, Girase, DeLorenzo, & Chapman, 2009) and retinopathy (Woung, Tsai, Chou, et al, 2010)) and related medical costs. For example, Woung et al (2010) reported significant increase of costs associated with diabetic retinopathy (US $1566in 2000to US $3326 in 2004).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Most existing studies have adopted the cross-section study design and reported only point estimates of annual prevalence of diabetic complications and associated costs (Chang, Weiner, Richards, Bleich, & Segal, 2012a;Rosenzweig, Weinger, Poirier-Solomon, & Rushton, 2002;Ward, Alvarez, Vo, & Martin, 2014). Furthermore, some of them were limited to specific diabetic complications (such as cardiovascular complications (Straka, Liu, Girase, DeLorenzo, & Chapman, 2009) and retinopathy (Woung, Tsai, Chou, et al, 2010)) and related medical costs. For example, Woung et al (2010) reported significant increase of costs associated with diabetic retinopathy (US $1566in 2000to US $3326 in 2004).…”
Section: Introductionmentioning
confidence: 96%
“…For example, Woung et al (2010) reported significant increase of costs associated with diabetic retinopathy (US $1566in 2000to US $3326 in 2004). Some studies also were limited to incremental costs between diabetic cohort and their non-diabetic counterparts only (Brown, Pedula, & Bakst, 1999;Farshchi, Esteghamati, Sari, et al, 2014;Straka et al, 2009;Woung et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…One study found the average cost of caring for patients with NPDR to be 292 USD, while it cost 1,207 USD to manage patients who develop PDR (6). Another study conducted by the National Health Services in Taiwan found that individuals who progressed from NPDR to PDR were noted to have an increase in expenditures of 3,482 USD (7). The ability for clinicians to identify and treat patients early in the disease process, before they experience progression to PDR, may result in considerable cost savings, especially in light of the growing number of individuals with diabetes mellitus (DM) in the U.S. population.…”
mentioning
confidence: 99%